1998
DOI: 10.1111/j.1471-0528.1998.tb09349.x
|View full text |Cite
|
Sign up to set email alerts
|

Is a rising caesarean section rate inevitable?

Abstract: Objective To determine the indications for singleton caesarean sections in Scotland in 1994.Design Prospective survey of singleton caesarean sections using information provided by clinicians Setting Twenty-three consultant-led obstetric units in Scotland.Population Women undergoing caesarean section in participating Scottish maternity units during 1994.Results Using routinely collected data it was found that the caesarean section rate varied by maternal age, parity, gestation, history of previous section and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 17 publications
(20 reference statements)
5
82
0
4
Order By: Relevance
“…During the last 40 years, the caesarean section rate increased significantly from 5% in the 70s, to over 50% in the 90s. The highest rates of caesarean section were observed in Italy (39%), Portugal (25%) and Switzerland (32%) [17,18]. In 1995, the rate of cesarean deliveries in the United States was 21%, while in 2007 it increased up to 31.8% [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…During the last 40 years, the caesarean section rate increased significantly from 5% in the 70s, to over 50% in the 90s. The highest rates of caesarean section were observed in Italy (39%), Portugal (25%) and Switzerland (32%) [17,18]. In 1995, the rate of cesarean deliveries in the United States was 21%, while in 2007 it increased up to 31.8% [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Estudo escocês mostrou que as principais indicações de cesárea em mulheres com apresentação pélvica foram a nuliparidade, cesárea prévia e multiparidade 10 . Não existem, contudo, evidências científicas concretas que suportem esta conduta.…”
Section: Discussionunclassified
“…20 Improved surgical techniques, availability of broad-spectrum antibiotics, blood transfusion facilities, intensive care units have made CS a safe procedure and there are maternal demands for CS of 23 to 38.9%, which has increased the incidence of CS. 21 It is reported that VBAC trials with proper selection criteria and proper monitoring protocols can help in reducing the rate of CS. 18,19 In our study the second largest contributor to the primary CS rate was foetal distress, 16% similar to other reports.…”
Section: Discussionmentioning
confidence: 99%